Long-term development of surgical outcome of laparoscopic sacrohysteropexy with anterior and posterior mesh extension - Rusavy, Zdenek; Grinstein, Ehud; Gluck, Ohad; Abdelkhalek, Yara; Deval, Bruno (International urogynecology journal, 2023)
INTRODUCTION AND HYPOTHESIS: Long-term durability and functional outcome of laparoscopic sacrohysteropexy (LSH) remains to be confirmed. We set out to assess the development of surgical outcome in women with increasing minimal follow-up. METHODS: All women after LSH with anterior and posterior mesh extension operated for advanced apical uterine prolapse at Geoffroy Saint-Hilaire clinic from July 2005 to June 2020 were enrolled in this retrospective study. Last known follow-up information was used for the analysis and allocation into groups. The surgical success was defined as no prolapse beyond hymen, no symptomatic recurrence or no retreatment. Functional outcome was evaluated from validated questionnaires and presence of pelvic floor disorders. The outcomes were compared with preoperative state using chi-square and Fisher's test; p < 0.05 was considered significant. RESULTS: In total, 270 patients after LSH with a follow-up of up to 14.5 years were enrolled and divided into groups according to their last follow-up length: ≥ 1 year 242, ≥ 3 years 112, ≥ 5 years 76, ≥ 7 years 45 and ≥ 10 years 18 women. Increase of minimal follow-up was associated with gradual decrease in surgical success. Rates of stress urinary incontinence were unchanged by the surgery, while anal incontinence and constipation rates decreased significantly; 14.5% of women were operated on for SUI in the follow-up. The PFDI-20, PFIQ-7 and VAS bother scores decreased significantly regardless of minimal follow-up length. CONCLUSIONS: LSH with anterior and posterior mesh extension is a safe, effective and durable surgery with a positive long-term effect on quality of life. Although the surgical success gradually decreases, LSH remains a surgical success in most women.
Keywords: Surgical success; Treatment Outcome; retrospektivní studie; prolaps pánevních orgánů; laparoskopie; Humans; gynekologické chirurgické výkony; Hysteropexy; Female; Laparoscopy; ženské pohlaví; Retrospective Studies; Pelvic Organ Prolapse; vagina; Quality of Life; Gynecologic Surgical Procedures; Vagina; Mesh; kvalita života; Follow-up; lidé; Surgical Mesh; chirurgické síťky; výsledek terapie